Implementation of Web Service Host To Host Payment for Pajak Bumi dan Bangunan Pekanbaru City - Wawan Kurniawan; Dadang Syarif Sihabudin Sahid (International ABEC, 2021)
Web service is an application of a collection of data (database), software (software) or part of software that can be accessed remotely by various devices with a certain intermediary. Web service can also be interpreted as a method of exchanging data, regardless of where a database is embedded, in what language an application that consumes data is made, and on what platform a data is consumed. Web services are able to support interoperability. So that the web service is able to become a bridge between the various existing systems.